Tawhidic-Communicative Gender Reconstruction: An Integration Model of Critical Social Theory and Islamic Philosophy in the Study of Gender Justice in Indonesian Pesantren - Ghozi, Ghozi; R, Mohammad Balyan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the reconstruction of gender justice at the Miftahul Ulum Al-Islamy Islamic Boarding School (Pesantren) through the intersection of critical social theory and contemporary Islamic philosophy. As a traditional institution, the pesantren occupies an ambivalent position: on one hand, it reproduces patriarchal structures through the authority of the kyai (religious leader) and the yellow books (classical Islamic texts); on the other hand, it holds transformative potential through the agency of the Nyai (female religious leader) and the reinterpretation of fiqh (Islamic jurisprudence) texts. Using a qualitative-philosophical approach with critical hermeneutic methods, this study synthesizes the thoughts of Foucault, Habermas, and the philosophy of tawhid (divine unity). Data were collected through curriculum analysis and in-depth interviews with Bu Nyai (the female religious leader) and students. The findings indicate that although the curriculum functions as a mechanism of gender discipline, there exists a dualism between hierarchical and egalitarian discourses. Here, the Nyai acts as an epistemic mediator who negotiates classical texts with contemporary realities, while tawhidic ontology and maqasid al-shariah (objectives of Islamic law) serve as the normative foundation for gender justice. As an original contribution, this study offers the Tawhidic-Communicative Gender Reconstruction model. This interdisciplinary integrative framework provides a new perspective in pesantren gender studies capable of bridging Islamic theology with modern communicative rationality to achieve a more systemically just educational order. [Penelitian ini mengkaji rekonstruksi keadilan gender di Pondok Pesantren Miftahul Ulum Al-Islamy melalui interseksi teori sosial kritis dan filsafat Islam kontemporer. Sebagai institusi tradisional, pesantren berada dalam posisi ambivalen: mereproduksi struktur patriarkal melalui otoritas kyai dan kitab kuning, sekaligus menyimpan potensi transformatif melalui agensi Nyai dan reinterpretasi teks fikih. Menggunakan pendekatan kualitatif-filosofis dengan metode hermeneutik kritis, studi ini mensinergikan pemikiran Foucault, Habermas, dan filsafat tauhid. Data dihimpun melalui analisis kurikulum dan wawancara mendalam bersama Bu Nyai serta santri. Temuan menunjukkan bahwa meskipun kurikulum berfungsi sebagai mekanisme disiplin gender, terdapat dualisme antara wacana hierarkis dan egaliter. Di sini, Nyai berperan sebagai mediator epistemik yang menegosiasikan teks klasik dengan realitas kontemporer, sementara ontologi tauhidik dan maqasid al-syariah menjadi fondasi normatif keadilan gender. Sebagai kontribusi orisinal, penelitian ini menawarkan model Tawhidic-Communicative Gender Reconstruction. Kerangka integratif interdisipliner ini memberikan perspektif baru dalam studi gender pesantren yang mampu menjembatani teologi Islam dengan rasionalitas komunikatif modern guna mewujudkan tatanan pendidikan yang lebih adil secara sistemik.]